Event-related EEG oscillations in body dysmorphic disorder. - Kapsali, Fotini; Zioga, Ioanna; Papageorgiou, Panos; Smyrnis, Nikolaos; Chrousos, George P; Papageorgiou, Charalabos (Eur J Clin Invest, 2020)
BACKGROUND: Patients with body dysmorphic disorder (BDD) exhibit differential attentional mechanisms compared to healthy subjects. The exact nature of this differentiation is unclear. To this end, EEG (electrophysiological) responses to prepulse inhibition (PPI: reflecting attentional modulation) and prepulse facilitation (PPF: indicating orienting activation) were recorded and analysed. The aim of this study was to compare the respective neural oscillations associated with PPI and PPF in BDD vs healthy controls. MATERIALS AND METHODS: Event-related EEG oscillations elicited by PPI and PPF (26 and 25 trials, respectively, randomly presented) were explored in a sample of patients with BDD (N = 30) vs healthy controls (N = 25). The Yale-Brown Obsessive-Compulsive Scale for BDD (BDD-YBOCS), the Body Dysmorphic Disorder Examination, the Dysmorphic Concern Questionnaire (DCQ) and the Brown Assessment of Belief Scale (BABS) were also administered. RESULTS: Analysis of the power spectrum in response to PPI and PPF revealed that the BDD patient group compared to healthy controls exhibited higher theta-1 oscillations (potentially indicative of disrupted thalamo-cortical activation) and reduced beta-1 oscillations (potentially indicative of reduced top-down-controlled processing during attentional orienting). CONCLUSION: These findings offer novel contributions with regards to the neural mechanisms underlying attention processes in BDD patients, and demonstrate the potential of event-related EEG oscillations as a tool to better understand body dysmorphic disorder.